Estudo da luminescência persistente em cerâmicas translúcidas de CaAl2O4:Eu2+,RE3+ sinterizadas a laser - Souza, Natalilian Roberta da Silva (2018)
Materials that present persistent luminescence have attracted a lot of attention due to their great potential in practical applications such as traffic signs, emergency signs, safety clothes, luminescent ceramics pigments and recently biological applications. More than two decades the calcium alumina (CaAl2O4 - CA) doped with Eu2 + and co-dopado with different ions has been studied for presenting a persistent luminescence greater than 10h. For this, several methods of synthesis and sintering have been applied. In this work were produced CA ceramics doped with me in different concentrations and co-dopadas with rare earths. The powders were produced by the method of polymeric precursors and ceramics sintered by a new method that uses a CO2 laser as the main source of heating. For the production and characterization of the samples, differential thermal analysis techniques, thermogravimetry, X-ray Difratometria, Raman spectroscopy, scanning electron microscopy, photoluminescence, optical transmittance and X-ray absorption were used. The laser sintered ceramics showed good homogeneity between the center and the edege, low porosity and transmittance from 45 to 70% in the range 400 to 900 nm. Through the results of Ramam spectroscopy and X-ray diffraction, the presence of a single crystalline phase was confirmed, indexed as a monoclinic P121 space group, which is indispensable to obtain persistent luminescence in the studied system. Through the photoluminescence spectrum it was observed that all samples presented emission at 440 nm characteristic of the transition 4f65d1-4f7 of the Eu in the studied matrix. The low temperature photoluminescence analyses suggest the occupation of Eu2 + in only two of the three possible sites, this fact may be related to the laser sintering process to be extremely fast. Through the spectrum of XANES was confirmed the presence of both the Eu2 + and the Eu3 + in all samples and that the amount of Eu3 + is higher. However, the ceramics presented a good persistent luminescence, with visible emission to the naked eye for several hours, being the sample doped with Nd that showed greater persistence.